Sustainability Accounting Practices in Social Enterprises in the Era of Circular Economy - Barnabas Tridig Silaban; Nur Nur; Tyara Angel Clarissa Tanujaya (Universitas Syiah Kuala, 2025)
The development of the circular economy requires accounting practices that are able to comprehensively record, measure, and report social and environmental impacts, especially in social enterprises that are oriented towards social missions in addition to economic goals. This research aims to explore sustainability accounting practices in social enterprises, focusing on how sustainability recording and reporting is carried out and the extent to which circular economy concepts influence the process. The research method used is a qualitative approach with a case study design, involving three social enterprises engaged in waste management and community empowerment in the Bandung area. Data was collected through in-depth interviews with 12 key informants, direct observation of operational activities, and analysis of internal documents, then analyzed using thematic analysis techniques. The results show that sustainability accounting practices are still in their early stages, characterized by informal recording of social and environmental contributions, despite a high awareness of the importance of transparency. The implementation of the circular economy encourages companies to integrate sustainability indicators into their reporting systems, although limited resources and technical capacity are major challenges. In conclusion, this study makes a theoretical contribution by expanding the understanding of sustainability accounting practices in the context of social enterprises, as well as practical contributions in the form of recommendations for strengthening accounting systems that are adaptive to circular economy principles to support long-term sustainability.